FRAKSI ETANOL EKSTRAK KULIT PISANG KEPOK KUNING ( Musa balbisiana) TERHADAP BAKTERI Staphylococcus epidermidis, Staphylococcus aureus, dan Propionibacterium acnes - Yuli Wahyu Tri Mulyani; Akhmad Rokiban; Galih Cipto Mahendra (Program Studi Farmasi Universitas Tulang Bawang, 2021)
Yellow kepok banana peel (Musa balbisiana) contains antibacterial compounds against S. epidermidis, S. aureus and P.acne. This study aims to proved the antibacterial activity of the yellow kepok banana peel extract fractionated using ethanol as a solvent against S.epidermidis, S.aureus and P.acne. The yellow kepok banana peel extraction process was carried out by maceration method with 70% ethanol followed by fractionation to obtain ethanol fraction. Antibacterial activity testing using nutrient agar (NA) media with wells method with a concentration of 25,000 ppm, 50,000 ppm, 100,000 ppm, aquadest as a negative control and clindamycin as a positive control. The phytochemical test of the ethanol fraction showed the content of alkaloids, flavonoids, saponins, tannins and quinones. The results of the inhibition zone diameter of the ethanol fraction at a concentration of 100,000 ppm against S. epidermidis (11.87 mm), S. aureus (12.04 mm) and P. acne (11.35 mm). The test is to determined the minimum inhibitory concentration (MIC) the minimum inhibitory concentration value of the ethanol fraction of S. epidermidis, S. aureus is 20,000 ppm and for P. acne is 17,500 ppm. The conclusion of this studied was that the ethanol fraction of kepok yellow banana peel extract has inhibitory and bacteriostatic properties against S. epidermidis, S. aureus and P.acne bacteria.Keywords: alkaloids,Ant ibacter ial , flavonoids , Fractionated, Musa balbisiana